Pour une histoire de la cartographie des territoires teko et wayãpi (Commune de Camopi, Guyane française) - Pierre Grenand; Françoise Grenand; Pierre Joubert; Damien Davy (Revue d'ethnoécologie)
This work is a sensibly modified version of the text published by the Guianese Amazonian Park for Wayãpi and Teko communities of the Oyapock and Camopi regions and for this region’s schools (Grenand et al. 2015). It is an analysis of the history and cartography of the Teko and Wayãpi territories, of the construction of natives’ toponymy, and finally a presentation selected toponyms highlightin both name memorization and location visualization.